BAZNAS STRATEGY FOR CAPITAL MARKET - Anita Anita (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2019)
Abstract. BAZNAS Strategy For Capital Market. BAZNAS as the institution for managing zakat also helped to bring Indonesia's capital market to international awards. Because, only the Indonesian capital market has been provided with philanthropy facilities. The concept of Islamic philanthropy applied to the Indonesia Stock Exchange is the result of collaboration between BAZNAS and PT. Henan Putihrai Securities. Furthermore, this paper aims to introduce of stock zakat and sedekah, including schemes and operational mechanisms of the program. Furthermore, the formulation of the discussion is: (1) The Meaning of Islamic Philanthropy, (2) The Concept of Philanthropy in the Capital Market, and (3) Schema and Mechanisms of stock Zakat and sedekah. Abstrak. Langkah Strategis BAZNAS Menuju Pasar Modal. Baznas sebagai lembaga untuk mengelola zakat juga membantu membawa pasar modal Indonesia ke penghargaan internasional. Sebab, hanya pasar modal Indonesia yang diberikan fasilitas filantropi. Konsep filantropi Islam yang diterapkan di Bursa Efek Indonesia adalah hasil kolaborasi antara BAZNAS dan PT. Henan Putihrai Securities. Selanjutnya, makalah ini bertujuan untuk memperkenalkan stok zakat dan sedekah, termasuk skema dan mekanisme operasional program. Selanjutnya, rumusan diskusi adalah: (1) Makna Filantropi Islam, (2) Konsep Filantropi di Pasar Modal, dan (3) Skema dan Mekanisme Stok Zakat dan Sedekah.